Silica Gel Supported Collidinium Chlorochromate: A New Reagent for Selective Oxidation of Benzylic Alcohols - VAHDAT, MOHAMMAD; TAJBAKHSH, MAHMOUD; BAHARFAR, ROBABEH; MOHANAZADEH, FARAJOLLAH; SHIRI, LOTFI (Asian Journal of Chemistry, 2010)
The new and mild chromium(VI) oxidant agent, collidinium (2,4,6- trimethylpyridinium) chlorochromate supported onto silica gel, was prepared as a stable yellow solid. The reagent is suitable for efficient and selective oxidation of benzylic alcohols to the corresponding carbonyl compuonds in excellent yields.